Strategies and Analysis of RERA across the ‘State Cluster’ of India - Rakeshkumar K. Tiwari, Krupesh A. Chauhan (International Journal of Advanced Science and Technology, 2020)
In India, the real estate sector has its own significance towards the development of economy. It is the foremost largest employment driver next to the agriculture. It is responsible for the growth of many auxiliary industries of construction materials. Quantum of this sector to gross domestic product is very difficult to calculate accurately but it contributes around 6%. The Indian real estate market is still in its childhood, unorganized and influenced by small players in a large number. Allocation of land is mainly managed by state government bodies. The previous governmental policies lead to significant losses to the nation. The main objective behind implementation of the Real Estate (Regulation and Development) Act 2016 was to bring more limpidity & accountability in the real estate sector. Each & every state was entitled to lay down its own laws as per guidelines prescribed by the central government to provide a united legal administration. In this paper investigations are made on the basis of formulation of provisions by various states to regulate RERA. It was analyzed and compared particularly for Maharashtra, Gujarat, Rajasthan and Madhya Pradesh. It is found that major points of disconnect between the state regulations and the central act guidelines Keywords: RERA, GDP, Indian Real Estate Sector, Employment, Analysis